Kepuasan Pelanggan di CV. Tirta Semesta Indonesia: Analisis Kualitas Pelayanan dan Harga - Syahri Romadhon; Esti Dwi Rahmawati; Taufiq Nur Muftiyanto (Jurnal Publikasi Ilmu Manajemen, 2024)
This study aims to determine the effect of service quality and price on customer satisfaction of CV. Tirta Semesta Indonesia. This study uses quantitative research methods. The population in this study were customers at CV. Tirta Semesta Indonesia and the number of samples in this study were 83 respondents using purposive sampling technique. The variables used in this study are service quality, price and customer satisfaction. The data used in this study are primary data. The data collection method used is a questionnaire through G-Form. The results of this study indicate that service quality has a positive and significant effect on customer satisfaction, and price has a positive and significant effect on customer satisfaction, and service quality and price simultaneously (together) affect customer satisfaction.